2009
DOI: 10.1039/b909551a
|View full text |Cite
|
Sign up to set email alerts
|

MRI contrast agent delivery using spore capsules: controlled release in blood plasma

Abstract: The exine coatings of spores can be used to encapsulate drug molecules. We have demonstrated that these microcapsules can be filled with a commercial gadolinium(III) MRI contrast agent (in this proof of concept study Gd-DTPA-BMA was used) which is slowly released in plasma due to enzymatic digestion of the capsule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 14 publications
1
40
0
Order By: Relevance
“…[30][31][32] Most conventional techniques used for encapsulation such as emulsion solvent evaporation, spray drying, and chemical conjugation fail to reliably provide either size monodispersity or well-defi ned microstructures. [ 26,27,[30][31][32] Although several studies have reported the use of empty exine microcapsules for the encapsulation of drugs, vaccines, and magnetic resonance imaging (MRI) contrast agents, as well as for use in cosmetics and food supplements, [ 7,[16][17][18]22 ] the use of the natural "spores" as a microencapsulation material and delivery vehicle still remains unexplored. In this regard, we have directed our efforts toward exploring systems to produce macromoleculeloaded spores using three different microencapsulation techniques.…”
Section: Doi: 101002/adfm201502322mentioning
confidence: 99%
“…[30][31][32] Most conventional techniques used for encapsulation such as emulsion solvent evaporation, spray drying, and chemical conjugation fail to reliably provide either size monodispersity or well-defi ned microstructures. [ 26,27,[30][31][32] Although several studies have reported the use of empty exine microcapsules for the encapsulation of drugs, vaccines, and magnetic resonance imaging (MRI) contrast agents, as well as for use in cosmetics and food supplements, [ 7,[16][17][18]22 ] the use of the natural "spores" as a microencapsulation material and delivery vehicle still remains unexplored. In this regard, we have directed our efforts toward exploring systems to produce macromoleculeloaded spores using three different microencapsulation techniques.…”
Section: Doi: 101002/adfm201502322mentioning
confidence: 99%
“…Thus overall, we hypothesized that if (i) natural pores in the pollen wall could be used to clean and remove the allergy-causing native biomolecules from PGs, (ii) their clean ‘belly’ could be refilled with vaccine antigens through the natural pores in pollen walls, and (iii) the antigen-filled PGs could translocate across the intestinal epithelium into the body, then PGs might behave as natural ‘Trojan horses’ for oral vaccination ferrying the vaccines safely into the body. While LSs can survive the harsh acidic treatment, it has been suggested that enzymes in the body can degrade them [18, 19], thus providing a potentially safe natural carrier for oral vaccine and drug delivery. Indeed, using this conceptual framework LSs have recently been proposed for oral drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, using this conceptual framework LSs have recently been proposed for oral drug delivery. It has been shown that proteins as large as 540 kDa, a magnetic resonance imaging contrast agent, food oils including cod liver oil can be filled into LSs [19-23]. While these in vitro studies demonstrate the flexibility of filling LSs with different molecules, in vivo demonstrations on the effectiveness of pollens for oral drug and vaccine delivery are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In order to address possible issues of biocompatibility and allergenicity, a protein-free microcapsule derivative known as a sporopollenin exine capsule (SEC) was developed through an extraction process that leaves only the hollow sporopollenin exine layer, which itself functions as a microcapsule and can be utilized for encapsulation applications151819202122. As a microcapsule, SECs have demonstrated great versatility for applications such as bioimaging23, taste masking19, and even cell seeding scaffolds20.…”
mentioning
confidence: 99%